Effects of a high-fibre and low-starch diet in growth performance, carcass and meat quality of young Alentejana breed bulls. (October 2020) - Santos-Silva, José; Alves, Susana P.; Francisco, Alexandra; Portugal, Ana Paula; Almeida, João; Fialho, Letícia; Jerónimo, Eliana; Bessa, Rui J.B.
Abstract: Growth performance, carcass and meat quality of 16 Alentejana bulls fed for 90 days with a conventional cereal-based (Control) or a high-fibre and low-starch (HFLS) diet were studied. The HFLS diet included 20% alfalfa hay, 4.8% soybean oil, 6% soybean hulls, 6% dehydrated citrus and 6% sugar beet pulps in substitution of grain. Ryegrass hay was offered to a maximum of 20% of total intake in both diets. Bulls were individually housed, weighed every 14 days, and feed intake was registered daily. Average daily weight gain, dry matter intake, carcass and most meat quality traits were not affected by the diet ( P  > .05). Feeding an HFLS diet, therefore, can improve beef fatty acid profiles without negatively impacting animal performance or meat quality. Highlights: Bulls fed a cereal-based diet or a low starch diet had similar growth performance. The high-fibre, low-starch diet improved beef meat oxidative stability during ageing. The high-fibre, low-starch diet improved beef meat fatty acid profile.